Toward Mobile-Assisted Language Learning (MALL): Reaping Mobile Phone Benefits in Classroom Activities - Rully Yudhiantara; Ihsan Abdul Nasir (Register Journal, 2017)
Mobile phone has been studied by researchers in its connection with education-related activies.  This study was aimed at investigating two research questions: 1) what are students’ perception toward mobile phone to support classroom activities; 2) How do students experience mobile phone use to support classoom activities? This study employed qualitative method. To collect data, there were some technique used: questionnaire and observation.  Students participated in this study were 70 students. Findings showed that student had positive perception and attitude toward mobile phone to support classroom activities. In classroom they used mobile phone to support classroom activitis. Reading E-Book that support subject, playing Audio and Video File, operating offline dictionary were activities supported by mobile phone use.